SEJARAH DAKWAH SULTAN SYARIF ABDURRAHMAN AL-QADRI: ISLAMISASI DI PONTIANAK - Zakaria Efendi (Jurnal Lektur Keagamaan, 2021)
This article attempts to explain the history of the da'wah of Sultan Syarif Abdurrahman Al-Qadri through the Kadriah Sultanate in carrying out Islamization in Pontianak. The success of the da'wah of Sultan Syarif Abdurrahman Al-Qadri in carrying out Islamization in Pontianak is closely related to the power factor. However, there is a significant role that paved the way for the establishment of the Kadriah Sultanate to reach the peak of its existence, namely the communication factor. The figure of a wise leader allows the influence of Islam to grow rapidly. This study uses a descriptive qualitative approach, and by reviewing the literature of previous studies in order to obtain data that supports in compiling a paper on the history of the da'wah of Sultan Syarif Abdurrahman Al-Qadri in carrying out Islamization in Pontianak. The results showed that: (1) The success of Sultan Syarif Abdurrahman Al-Qadri's da'wah in carrying out Islamization in Pontianak was due to the influence of power. (2) The Sultanate became an effective da'wah media, because the Sultanate became the holder of political and economic power who had the authority to regulate policies in the area of ​​power that contributed greatly to spreading Islamic teachings (3) The acculturation approach of culture in spreading Islam among local communities became the right strategy used Sultan Syarif Abdurrahman Al-Qadri in carrying out Islamization in Pontianak. Until now, there have been many studies conducted with the object of the Kadriah Sultanate which was once the center of Islamic government in Pontianak. Among them are studies that have been carried out by Alfan Firmanto who wrote about "Historical Traces of the Pontianak Sultanate", by conducting a study of inscriptions on the Batu Layang tomb site which is the burial place of the Kadriah Sultanate family. This study emphasizes the communication element as a study in writing the history of Sultan Syarif Abdurrahman Al-Qadri in carrying out Islamization in Pontianak, the communication element includes how da'wah is carried out, what media is used, and what factors are behind the success of Sultan Syarif Abdurrahman Al-Qadri in the process of Islamization in Pontianak. Keywords: Da'wah, History, Islamization, Kadriah Sultanate, Pontianak.   Artikel ini berupaya menjelaskan sejarah dakwah Sultan Syarif Abdurrahman Al-Qadri melalui Kesultanan Kadriah dalam melakukan Islamisasi di Pontianak. Keberhasilan dakwah Sultan Syarif Abdurrahman Al-Qadri dalam melakukan Islamisasi di Pontianak sangat berkaitan erat dengan faktor kekuasaan. Namun ada peran signifikan yang membuka jalan bagi berdirinya Kesultanan Kadriah hingga mencapai puncak kejaannya adalah faktor komunikasi. Sosok pemimpin yang bijaksana membuat pengaruh Islam dapat berkembang dengan pesat. Kajian ini menggunakan pendekatan kualitatif deskriptif, dan dengan mengkaji literatur-literatur terdahulu agar memperoleh data yang mendukung dalam menyusun artikel tentang sejarah dakwah Sultan Syarif Abdurrahman Al-Qadri dalam melakukan Islamisasi di Pontianak. Hasil kajian menunjukkan bahwa: (1) Kesuksesan dakwah Sultan Syarif Abdurrahman Al-Qadri dalam melakukan Islamisasi di Pontianak adalah karena pengaruh kekuasaan. (2) Kesultanan menjadi media dakwah yang efektif, karena Kesultanan menjadi pemangku Kekuasaan politik dan ekonomi yang mempunyai wewenang mengatur kebijakkan di wilayah kekuasaan berkontribusi besar dalam menyebarkan ajaran Islam (3) Pendekatan akulturasi kebudayaan dalam menyebarkan agama Islam dikalangan masyarakat lokal menjadi strategi jitu yang digunakan Sultan Syarif Abdurrahman Al-Qadri dalam melakukan Islamisasi di Pontianak. Sampai saat ini sudah banyak kajian yang dilakukan dengan objek Kesultanan Kadriah yang pernah menjadi pusat pemerintahan Islam di Pontianak. Di antaranya adalah kajian yang pernah dilakukan oleh Alfan Firmanto yang menulis tentang “Jejak Sejarah Kesultanan Pontianak”, dengan melakukan kajian Inskripsi pada situs makam Batu Layang yang menjadi tempat pemakaman keluarga Kesultanan Kadriah. Artikel ini lebih menekankan pada unsur komunikasi sebagai kajian dalam menulis tentang sejarah Sultan Syarif Abdurrahman Al-Qadri dalam melakukan Islamisasi di Pontianak, unsur komunikasi mencakup bagaimana dakwah dilakukan, media apa yang digunakan, dan faktor apa saja yang melatarbelakangi kesuksesan Sultan Syarif Abdurrahman Al-Qadri dalam proses Islamisasi di Pontianak. Kata kunci: Dakwah, Islamisasi, Kesultanan Kadriah, Sejarah, Pontianak.